An exploration of perceptions of flourishing and social determinants of health among medical, physician assistant, and nurse practitioner students: A mixed methods study - Stephanie Neary; Benjamin Doolittle; Martina Mueller; Michelle Nichols (PLoS ONE, 2026)
The purpose of this study is to describe individual perceptions of flourishing among medical (MD), physician assistant (PA), and nurse practitioner (NP) students and the relationship between these perceptions and social determinants of health (SDOH). MD, PA, and NP students from two universities were recruited to participate in this explanatory sequential mixed-methods study. The quantitative phase took place between August and October 2023, and findings were used to purposively recruit participants for interviews that were conducted in January and February 2024. The survey included the WellRx and the Secure Flourish Index (SFI); participants applied a percentage weight (0–100%) to each of the six SFI domains of flourishing based on their perceived relative importance to their individual flourishing. Survey participants were stratified into three SDOH risk levels based on WellRx score; descriptive statistics and ANOVA testing were performed (alpha = 0.05). Interviews explored definitions of flourishing, perceptions of flourishing domains, and how SDOH needs relate to flourishing. A total of 280 of 1820 eligible students (15.4%) completed the survey, and 34 students across all three established SDOH risk groups were interviewed. Results demonstrated a significant relationship between SDOH factors and flourishing perceptions. Low-risk group students had an average SFI score that was over 15.0 points greater than those in the high-risk group (M88.0(SD ± 14.4) versus M72.7(SD ± 13.5); p < .001). Perceived relative domain importance to flourishing significantly varied by SDOH risk level for multiple domains. Participant definitions of flourishing included elements of personal growth and a balance of happiness and success; interviews revealed that students in all SDOH risk levels are experiencing financial strain that negatively impacts flourishing across SFI domains. Perceptions of flourishing and the relative importance of established flourishing domains are highly influenced by social determinants of health and living experiences. Educators should consider individual perspectives and values when measuring flourishing and planning wellness interventions.